2019
DOI: 10.1093/sleep/zsz171
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Magnetic Resonance Imaging reveals alterations of sensorimotor circuits in restless legs syndrome

Abstract: Study Objectives Integrated information on brain microstructural integrity and iron storage and its impact on the morphometric profile is not available in restless legs syndrome (RLS). We applied multimodal magnetic resonance imaging (MRI) including diffusion tensor imaging, the transverse relaxation rate (R2*), a marker for iron storage, as well as gray and white matter volume measures to characterize RLS-related MRI signal distribution patterns and to analyze their associations with clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 56 publications
2
26
0
Order By: Relevance
“…Several DTI studies of RLS reported alterations of motor and somatosensory systems, but the details of the results have been different among studies. Some studies reported decreased FA values in variable supratentorial WM tracts including WM close to the motor and somatosensory cortices, CG, putamen, genu of the corpus callosum, and internal capsule 6 , 8 , 12 . Two studies reported involvement of infratentorial structures such as brain stem, cerebellum, and upper cervical cords in RLS patients 9 , 10 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several DTI studies of RLS reported alterations of motor and somatosensory systems, but the details of the results have been different among studies. Some studies reported decreased FA values in variable supratentorial WM tracts including WM close to the motor and somatosensory cortices, CG, putamen, genu of the corpus callosum, and internal capsule 6 , 8 , 12 . Two studies reported involvement of infratentorial structures such as brain stem, cerebellum, and upper cervical cords in RLS patients 9 , 10 .…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancies between results might be explained by differences in post-processing methodologies between studies and the technical limitations of these previous methods. These studies used voxel-based approaches 6 , 8 10 , 12 or the TBSS method 7 , 11 , which resulted in mixed values for multiple fiber tracts with different orientations. Differences in sample size, magnetic field strength, and rate of possible comorbid sleep disorders also might have contributed to the discrepancies between results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is likely that impulsive choices, as demonstrated by the beads task, are due to neuroplastic changes caused by long-term dopaminergic medication similar to what has been described in patients with Parkinson’s disease and ICDs [ 14 , 21 ]. One study on multimodal MR imaging in RLS identified higher connectivity within the left executive network, associated with attention, working memory, and decision making [ 22 ]. Interestingly, in our study additional presence of an ICD symptom did not worsen performance on the beads task.…”
Section: Discussionmentioning
confidence: 99%